2020
DOI: 10.5194/egusphere-egu2020-19755
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Auroral omega bands are a significant cause of large geomagnetically induced currents

Abstract: <p>The strongest event of geomagnetically induced currents (GIC) detected by the North-West Russian GIC network occurred during the main phase of the magnetic storm on June 28-29, 2013. Extremely high values, 120 A, were recorded in the 330 kV transformers on Kola Peninsula in the 04--07 magnetic local time (MLT) sector. The Defense Meteorological Satellite Program (DMSP) spacecraft took a sequence of ultraviolet (UV) auroral images in the southern hemisphere and observed multiple omega bands. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 0 publications
1
35
0
Order By: Relevance
“…The field of view of the auroral imager moved successively farther west with each successive orbit because of Earth's rotation relative to a fixed orbital plane. As was the case for the event studied by Apatenkov et al (2020), these images show that omega bands along the morning sector auroral oval were evident both before and during the 05–08 UT interval of MPEs shown in Figures 11 and 12.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The field of view of the auroral imager moved successively farther west with each successive orbit because of Earth's rotation relative to a fixed orbital plane. As was the case for the event studied by Apatenkov et al (2020), these images show that omega bands along the morning sector auroral oval were evident both before and during the 05–08 UT interval of MPEs shown in Figures 11 and 12.…”
Section: Discussionsupporting
confidence: 78%
“…In contrast, within the postmidnight interval sharp pulses were seen at different times at each site over a span of ~1.5 hr. Their multiple rapid variations resembled those of Pi 3 or Ps 6 pulsations (Apatenkov et al, 2020; Opgenoorth et al, 1983; Solovyev et al, 1999) rather than solitary impulses.…”
Section: Event Studiesmentioning
confidence: 81%
See 1 more Smart Citation
“…2006; Weigel et al., 2003). In addition to these, auroral omega bands are another phenomenon which can be responsible for large d B /d t and GIC events (Apatenkov et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Though the power of such processes is much lower than the power of magnetospheric storms and substorms, the rapidly varying electromagnetic fields of these disturbances can induce a significant GIC (Apatenkov et al, 2004;Belakhovsky et al, 2018;Viljanen, 1998). The events were presented when the ULF variations of the Pi3 or Ps6 type induced GIC in power transmission line up to 120 A (Apatenkov et al, 2020;Belakhovsky et al, 2019). Viljanen et al (2001) suggested that the Pc5 waves during the recovery phase of a magnetic storm may cause intense GICs.…”
Section: Introductionmentioning
confidence: 99%